ANALISIS METODE ROLE PLAYING DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA PADA BANGUN DATAR PESERTA DIDIK KELAS V SD - Puspita, Rena; Trisiana, Anita; Rizkasari, Elinda (Universitas Negeri Medan, 2025)
This research method is qualitative to identify students' abilities in learning mathematical story problems on plane figures through role-playing method in fifth grade of SD Negeri Karangasem 1 Surakarta. Data were collected through observation, interviews, and documentation. The results showed a significant improvement in students' ability to solve mathematical story problems on plane figures after the application of the role-playing method. The average student score increased from 70 to 90, reflecting substantial understanding. Observations showed that students who participated in role-playing were more active, asked more questions, and were more enthusiastic. Students' responses to this method were very positive, with many feeling interested in learning mathematics. Students considered the role-playing stories relevant to everyday life, helping them understand mathematical concepts in real situations. Despite challenges in conveying complex stories and variations in students' abilities, the results showed that the role-playing method was effective for mathematics learning in SD Negeri Karangasem 1 Surakarta. This study recommends the continuous application of the role-playing method and the adjustment of stories according to students' needs and backgrounds to improve learning effectiveness.